The flow of funds 1972-1977 - Honohan, Patrick; Dunne, John (Statistical and Social Inquiry Society of Ireland, 1982)
Corresponding to the existence of financial assets there is the phenomenon of saving and dissaving, of financial surpluses and deficits. We may say that whenever an economic agent spends, over a certain period, more than his income on goods and services, he is dissaving and is a net issuer of financial assets: he is accumulating financial liabilities. The questions addressed by a flow of funds analysis are: how much financial saving or dissaving has been undertaken by various classes of agents; and which assets and liabilities have they accumulated over a given period?
Read before the Society, 22 April 1982
Keywords: Flow of funds, Ireland; Government budget; Private saving; Current account balance; 314.15